Studi Kasus: Penerapan Terapi Murottal Surah Ar-Rahman Terhadap Kualitas Tidur Pada Lansia Dengan Insomnia Akut - Suparto, Tirta Adikusuma; Puspita, Asih Purwandari Wahyoe; Siti Nurkhafipah, Anida; Sutrisno, Imam Tri (Yayasan Healing and Healthcare Education, 2024)
The problem that is often experienced among the elderly at this time is having difficulty sleeping. One that occurs in the elderly is the occurrence of insomnia. Insomnia can be overcome by giving murottal therapy. Murottal is the chanting of the holy verses of the Koran which is recorded and played at a slow and harmonious tempo so that it can increase relaxation and improve the circadian rhythm of the elderly so that their sleep quality improves. This research method uses a qualitative descriptive method using a case study approach with two subjects aged 60 years and over who experience insomnia. The intervention carried out is murottal therapy surah ar-rahman which is carried out for 6 consecutive days with a duration of 15 minutes carried out at PTSW Budi Pertiwi from June 20-26, 2023. Assessment of insomnia scores using the Insomnia Rating Scale Assessment. From this study, it was found that murottal therapy can improve sleep quality so that there is a decrease in scores from scores 13-18 (moderate insomnia) to <8 (no insomnia). Based on the conclusion, there is an improvement in the sleep quality of the two respondents, where respondent 1 experienced a decrease in score from score 13 to score 4 and respondent 2 from score 14 to 7. It is proven that murottal therapy can improve sleep quality in the elderly.